Educação ambiental em uma escola de tempo integral ambiental: a construção coletiva de uma trama formativa - Miranda, Raquel Sales (2022)
The focus of this research is the collective construction of a formative web that involves Environmental Education (EE), in Kindergarten and Early Years of Primary Education, practiced in a Full Time Environmental School. Besides the personal identification with the research theme, the environmental crisis that has worsened in recent years in the Brazilian context has strengthened the idea of researching how teachers have dealt with these issues in schools and how a continuing education could contribute to the practice of these teachers. In this context, the question arose: How can freirean awareness contribute to the training of managers and teachers who already perform actions and practices of Environmental Education in Full Time Environmental School? To answer this question, this work started from the following thesis: The initial training of teachers who work in Environmentally Curricular Schools does not give support for them to promote an emancipatory and critical environmental education, so the continuing education of teachers, in a perspective of awareness and participation, contributes to strengthen this training. Thus, the central objective of this research was: To reflect on the development of a continuing education for teachers and managers in EE, from the perspective of freirean awareness, starting from the understanding of how it develops EE in a municipal full-time environmental public school. The specific objectives were: 1. to identify how the environmental identity of the school has been built; 2. to verify how the EE is effective in everyday school, from the practices of teachers and managers and; 3. to reflect on the practices of EE teachers and managers of the institution, through a continuing education, based on freirean awareness. The approach of this research was qualitative and the method used was action research-participant. This study was carried out in a Full-Time Environmental School and, for data collection: document analysis, semi-structured interview, questionnaire and participant observation. After the survey of the themes of interest for the formation of teachers and managers of the Full-Time Environmental School, 20 hours of formative activities were carried out through Google Classroom, and 20 hours of synchronous meetings through Google Meet, for a target audience of 19 participants (16 teachers and 3 managers). From the Textual Discourse Analysis (TDA), emerged as final categories of analysis: the formation of environmental identity of the school institution; reflections on the practices of EE in the School Institution; the construction of the viable unpublished. With the development of research, we realize that the environmental identity of the school institution is constituted as a web still under construction, and some factors hinder the strengthening of environmental identity of the school, such as its classification as a Full-Time School, the little presence of EE in school documents and the lack of initial and continuing education in relation to EE. Thus, although the school is managing to establish an environmental fabric, some points are not yet well established. In relation to as practiced in the school environment, we noticed that As is present in the institution in different ways, however, there is a focus on conservationist and pragmatic EE. Thus, we understood that it was still necessary to advance a little more in relation to the reflection on The Freiriana Environmental Education (FEE). Thus, several moments were opportunistic so that the participants could reflect on their actions of EE, in order to enable them to be reaching the level of awareness from the denunciation of the limit situations faced in the realization of EE in the school environment. And finally, in order to achieve the last stage of Freiriana awareness, the participants of the formation built an Environmental Agenda for the school institution. We noticed some indications of advances in the participants' awareness regarding the more complex perception of the environment, the importance of politics, dialetization and the Freriana approach in Environmental Education. However, we understand that although awareness is facilitated in collective discussions, it is a process that occurs differently for each individual. We emphasize that the plot that was built does not end with the publication of this thesis, it will continue in the actions of the Extension Project linked to the Pro-Rectory of Extension-UFC and can still be carried out future work involving EE practices with children and activities focused on the ‘Parque Estadual do Cocó’.